30 nm X-ray focusing correlates oscillatory stress, texture and structural defect gradients across multilayered TiN-SiOx thin film. (1st February 2018) - Keckes, J.; Daniel, R.; Todt, J.; Zalesak, J.; Sartory, B.; Braun, S.; Gluch, J.; Rosenthal, M.; Burghammer, M.; Mitterer, C.; Niese, S.; Kubec, A.
Abstract: Resolving depth gradients of microstructure and residual stresses within individual sublayers of multilayered thin films and understanding their origin as well as their influence on functional properties are challenging tasks. In this work, a newly developed synchrotron focusing setup based on Multilayer Laue Lenses, providing an X-ray beam diameter of ∼30 nm, is used to characterize the cross-sectional properties of a 2.9 μm thick sculptured multilayered TiN-SiOx film, which consists of twelve ∼230 nm thick nano-crystalline TiN sublayers of zigzag columnar grain morphology separated by eleven amorphous SiOx sublayers, both prepared by oblique magnetron sputtering on a Si(100) substrate. The X-ray nano-diffraction analysis of the TiN sublayers reveals (i) an oscillatory variation of compressive residual stresses across the film ranging between −1.8 and −0.25 GPa, (ii) the presence of <100> fiber textures with three different fiber axis orientations, which abruptly change between the individual sublayers, and (iii) gradually decreasing densities of structural defects within every TiN sublayer, exhibiting a sawtooth-like depth-profile across the film. The near-substrate TiN sublayer shows the highest compressive stress reaching ∼ −1.8 GPa, a unique texture and the largest density of defects among all sublayers, which indicates diverse nucleation mechanisms of TiN on the native Si oxide and on the SiOx sublayers. The results demonstrate that the average stress state and the microstructure within the individual TiN sublayers can be influenced effectively by the applied deposition conditions, although self-organization processes during the sublayers' evolution give rise to the occurrence of qualitatively similar gradual trends, which differ in intensity and which were characterized also by complementary laboratory X-ray diffraction, as well as scanning and transmission electron microscopies. Finally, the presented results document that the novel X-ray nano-probe approach allows for the characterization of nano-scale gradients within individual microstructural features of polycrystalline thin films and pioneers the way for knowledge-based synthesis of thin films with predefined cross-sectional microstructure and property gradients. Graphical abstract: Image 1